High school students' social media use predicts school engagement and burnout: the moderating role of social media self-control - Du, Jie; Wang, Yu (Frontiers in Child and Adolescent Psychiatry, 2024)
Students' social media use has quickly gained attention given the effect of considerable time spent on and widespread usage of social media on their development and success. The study aimed to examine whether high school students' social media use predicts more school engagement and less burnout for those who were more successful in controlling their social media use in goal-conflict situations. A sample of 107 Chinese high school students (Mage = 19.21, SDage = 1.85, 68% female) participated in an online survey. The results showed that social media self-control failure moderated the relationship between general social media use (rather than social media use intensity) and school engagement. A simple effect test revealed that more general social media use predicted higher school engagement for students who were more successful in controlling their social media use. However, no moderation effect was observed of social media self-control failure on the relationship between social media use intensity (or general social media use) and burnout. The results partially supported the study demands-resources model and indicated the potential benefits of controllable social media use on high school students’ engagement in the face of high academic demands.